(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objectives: To evaluate the relationship between tongue characteristics and Traditional Medicine body constitution types in healthy volunteers from the Faculty of Traditional Medicine (TM) in the University of Medicine and Pharmacy at Ho Chi Minh City (UMP). Subjects and research methods: The cross-sectional study of 424 TM students at the UMP was conducted from January to April 2024. Primary outcome variables included body constitution (BC) types (via the Vietnamese version of the Constitution in Chinese Medicine Questionnaire), and tongue characteristics (extracted by ZMT-1A machine). Chi-square tests were used to analyze relationships between BC types and tongue characteristics. Results: Distribution analysis showed that the Neutral constitution was the most common (64.6%). BC types related with tongue body characteristics include color, size, fissures, and papillae (p <0.05); BC types also correlated with tongue coating characteristics include color, thickness, moisture, and dirty level (p<0.05). Specifically, Yin-deficiency, Qi-deficiency, and Dampness-heat constitutions showed pink to dark red body tongue. Yang-deficiency, Yindeficiency, Dampness-heat, and Blood-stasis displayed tongue fissures, while papillae only appeared in Dampness-heat. Dampness-heat showed a yellowish-white coating. Additionally, moist tongue coating was predominantly found in Yang-deficiency, Qi-deficiency, Dampness-heat, and Blood-stasis types. Conclusions: Tongue diagnosis – including tongue body color, papillae, fissures, coating color, and moisture level – provides a rapid assessment of TM BC and thus indicates trends in disease development. This enables physicians to guide individuals in targeted lifestyle changes to improve their quality of life.